2022
DOI: 10.3389/fcell.2021.759354
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Approach to Unveil Key Differentially Expressed Proteins in Human Sperm After Slow and Rapid Cryopreservation

Abstract: Currently, two conventional freezing techniques are used in sperm cryopreservation: slow freezing (SF) and rapid freezing (RF). Despite the protocolar improvements, cryopreservation still induces significant alterations in spermatozoon that are poorly understood. Here, available proteomic data from human cryopreserved sperm was analyzed through bioinformatic tools to unveil key differentially expressed proteins (DEPs) that can be used as modulation targets or quality markers. From the included proteomic studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…Moreover, in these studies, a change in sperm proteomic profile has been reported not only by comparing fresh and frozen spermatozoa but also by evaluating different methods, steps and actors involved in the cryopreservation process [121,124]. Differentially expressed proteins have been found by examining both different preservation methods, such as slow or rapid freezing and vitrification [125,126], and by modifying freezing/thawing conditions [121], as well as by using different types of cryoprotectants [121] or different cryopreservation carriers (cryovials or cryostraws [124]). Although the identity of most of the up-or down-regulated proteins found in the different experimental conditions varies in these studies, they are almost always involved in important sperm functions for achieving oocyte fertilization, such as energy production, motility, apoptosis, DNA damage and repair, capacitation, acrosome reaction, sperm-egg fusion, etc.…”
Section: Damage To Mrnas Proteins and Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in these studies, a change in sperm proteomic profile has been reported not only by comparing fresh and frozen spermatozoa but also by evaluating different methods, steps and actors involved in the cryopreservation process [121,124]. Differentially expressed proteins have been found by examining both different preservation methods, such as slow or rapid freezing and vitrification [125,126], and by modifying freezing/thawing conditions [121], as well as by using different types of cryoprotectants [121] or different cryopreservation carriers (cryovials or cryostraws [124]). Although the identity of most of the up-or down-regulated proteins found in the different experimental conditions varies in these studies, they are almost always involved in important sperm functions for achieving oocyte fertilization, such as energy production, motility, apoptosis, DNA damage and repair, capacitation, acrosome reaction, sperm-egg fusion, etc.…”
Section: Damage To Mrnas Proteins and Metabolitesmentioning
confidence: 99%
“…Some of these proteins could be revealed as potential markers of sperm freezability once validation studies are performed. An example is represented by the Arylsulfatase A, a protein implicated in gametes fusion, whose levels decreased after both slow-and rapid-freezing, suggesting that it could be used as a marker of sperm quality after cryopreservation [126,127]. Of note, it has been reported that oncological patients show already altered proteomic profiles before cancer treatments [128][129][130] and, therefore, at the moment of cryopreservation.…”
Section: Damage To Mrnas Proteins and Metabolitesmentioning
confidence: 99%
“…In these proteomic studies, ejaculated spermatozoa from normozoospermic and infertile men were compared to identify differentially expressed proteins (DEPs). Through bioinformatic workflows, the DEPs are analysed to unveil altered pathways and defective biological processes allowing the molecular understanding of deregulated mechanisms [ 16 17 ]. Such bioinformatics analyses are also useful to identify potential biomarkers and therapeutic targets for subsequent investigation [ 17 18 ].…”
Section: Introductionmentioning
confidence: 99%